A perspectiva sociocrítica da modelagem matemática e a aprendizagem significativa crítica : possíveis aproximações - Silva, Cíntia da (2011)
The study of theoretical frameworks that deal with the sociocritical prospect of Mathematical Modelling pointed out some similarities in some respects, with the Critical Theory of Meaningful Learning. Accordingly, this research aims to determine the possible equivalence between the sociocritical perspective of Mathematical Modelling and the Critical Meaningful Learning, as well as identifying evidence indicating that modeling activities in this perspective can promote the occurrence of Meaningful Learning Critique. Aiming to achieve the proposed objectives, we make use of the methodology of textual discourse, through which it was possible to identify four elements that characterize descriptive, specifically, an activity of Mathematical Modeling in sociocritical perspective, based on some major theoretical frameworks already published on this topic. These characteristics were used to analyze all the reports presented at the VI CNMEM experience about their environment from this perspective. Following the reports classified as belonging to the perspective of modeling sociocritica were analyzed according to the principles of Meaningful Learning facilitators Critique. The results allow us to conclude that specific actions in the modeling activities can help the prospect sociocritica Meaningful Learning Critique.